An Intramolecular Interaction between Src Homology 3 Domain and Guanylate Kinase-Like Domain Required for Channel Clustering by Postsynaptic Density-95/SAP90 - Shin, Hyewon (J Neurosci, 2000)
Members of the postsynaptic density-95 (PSD-95)/SAP90 family of membrane-associated guanylate kinase (MAGUK) proteins function as multimodular scaffolds that organize protein-signaling complexes at neuronal synapses. MAGUK proteins contain PDZ, Src homology 3 (SH3), and guanylate kinase (GK)-like domains, all of which can function as sites for specific protein–protein interactions. We report here a direct protein–protein interaction between the SH3 domain and the GK region in the PSD-95 family of MAGUKs. The SH3 domain of the PSD-95 family appears to have an atypical binding specificity, because the classical SH3 binding (-P-X-X-P-) motif is absent from the GK domain. Although SH3–GK binding can occur in either an intramolecular or intermolecular manner, the intramolecular mode is preferred, possibly because of additional tertiary interactions available when the SH3 and GK domains are adjacent in the same polypeptide. Mutations disrupting the intramolecular SH3–GK interaction do not interfere with PSD-95 association with the K(+) channel Kv1.4 or with the GK domain-binding protein GKAP. The same mutations, however, inhibit the clustering of Kv1.4 by PSD-95, suggesting that the intramolecular SH3–GK interaction may modulate the clustering activity of PSD-95.